Human Resource Development for Quality Potato Production and Post-harvest Management: An Evaluation - Dhiraj K. Singh and N.K. Pandey, (Indian Journal of Extension Education, 2018)
ICAR-Central Potato Research Institute, Shimla regularly organizes 21 days Summer School training course on quality potato production for scientists/teachers/extension functionaries of ICAR institutes, SAUs and KVKs located in different states of India. The current study was undertaken to evaluate the impact of Summer school on the knowledge and skill enhancement of trainees and overall evaluation of the training programme. Data were collected on different aspects on conduct and impact of training using a questionnaire which was administered before and after the conduct of the training programme. Results of the study revealed that training had significant impact on enhancing the knowledge level of participants in all areas of potato technologies. Average enhancement in knowledge was estimated to be 25.7 per cent. Majority of the participants expressed that they learned new skills in different areas of potato R&D. Most of the respondents were very well satisfied with the behaviour and style of teaching, course contents and training delivery methods. More than half of the participants graded training course as very good.